Effects of kinesio taping therapy on gait and surface electromyography in stroke patients with hemiplegia - Chen, Ze; Li, Min; Cui, Hongxing; Wu, Xipeng; Chen, Fangmin; Li, Wei (Frontiers in Physiology, 2022)
Background: The application of Kinesio Taping (KT) on the lower extremity of stroke patients can improve the quality of somatosensory information by activating lower extremity muscles involved in postural control. Gait analysis and surface electromyography (SEMG) are valuable in assessing the motor ability of the lower extremities. Objective: This study aimed to investigate the effects of KT therapy on gait and SEMG in stroke patients with hemiplegia. Methods: Twenty-one stroke patients were included in the study. KT was applied to the lower extremities of the hemiplegic side. Quantitative gait parameters were measured by a gait analysis system (IDEEA, by MiniSun, USA) and activation of the lower extremity muscles were evaluated by the SEMG (TrignoTM Wireless Systems, Delsys Inc., USA) before and after taping. Step length, stride length, pulling acceleration, swing power, ground impact, and energy expenditure were used to evaluate when patients walk as usual. SEMG signals were collected from the anterior bilateral tibialis (TA) and the lateral gastrocnemius (LG). The root mean square (RMS) value was used to assess muscle activity. SEMG signals were examined before and after KT treatment in three different locomotor conditions of the patients: walking at a natural speed, walking with a weight of five kilograms, dual-tasking walking (walking+calculation task) while carrying a weight of five kilograms. The calculation task was to ask the patients to calculate the result of subtracting 7 from 100 and continuing to subtract 7 from the resulting numbers. Comparisons between two normally distributed samples (before and after KT treatment) were evaluated using the two-tailed, paired Student’s t-test. Results: Stride length (0.89±0.19 vs 0.96±0.23; P=0.029), pulling acceleration (0.40±0.21 vs 1.11±0.74; P=0.005), and swing power (0.42±0.24 vs 1.14±0.72; P=0.004) improved in the hemiplegia side after KT treatment. The RMS value of TA SEMG signals in the limbs on the hemiplegia side decreased after KT treatment during dual-tasking walking carrying a weight of five kilograms (3.65±1.31 vs 2.93±0.95; P=0.030). Conclusions: KT treatment is effective in altering gait and SEMG characteristics in stroke patients with hemiplegia.